Improved Protective Effect of Umbilical Cord Stem Cell Transplantation on Cisplatin-Induced Kidney Injury in Mice Pretreated with Antithymocyte Globulin - Željka Večerić-Haler; Andreja Erman; Anton Cerar; Helena Motaln; Katja Kološa; Tamara Lah Turnšek; Snežna Sodin Šemrl; Katja Lakota; Katjuša Mrak-Poljšak; Špela Škrajnar; Simona Kranjc; Miha Arnol; et al. (Stem Cells International)
Mesenchymal stem cells (MSCs) are recognised as a promising tool to improve renal recovery in experimental models of cisplatin-induced acute kidney injury. However, these preclinical studies were performed on severely immunodeficient animals. Here, we investigated whether human umbilical cord derived MSC treatment could equally ameliorate acute kidney injury induced by cisplatin and prolong survival in mice with a normal immune system and those with a suppressed immune system by polyclonal antithymocyte globulin (ATG). We demonstrated that ATG pretreatment, when followed by MSC transplantation, significantly improved injured renal function parameters, as evidenced by decreased blood urea nitrogen and serum creatinine concentration, as well as improved renal morphology. This tissue restoration was also supported by increased survival of mice. The beneficial effects of ATG were associated with reduced level of inflammatory protein serum amyloid A3 and induced antioxidative expression of superoxide dismutase-1 (SOD-1), glutathione peroxidase (GPx), and hem oxygenase-1 (HO-1). Infused MSCs became localised predominantly in peritubular areas and acted to reduce renal cell death. In conclusion, these results show that ATG diminished in situ inflammation and oxidative stress associated with cisplatin-induced acute kidney injury, the effects that may provide more favourable microenvironment for MSC action, with consequential synergistic improvements in renal injury and animal survival as compared to MSC treatment alone.